Suscetibilidade magnética e análise de incertezas em mapeamento de solos - Teixeira, Daniel De Bortoli [UNESP] (2015)
The lack of information on spatial variability of soil attributes is one of the limiting factors for the development of different areas of knowledge and productive sectors. This information and the knowledge of their uncertainties allow the correct interpretation of results and possible decision making. The study was conducted in two stages: the first stage aimed to use geological, geomorphological, and pedological information in order to reduce the sampling density needed for the spatial characterization of magnetic susceptibility (MS), clay content and base saturation (BS); the second stage aimed to use the spatial uncertainty of MS and clay content for the delineation of mapping units. The study area, located in the municipality of Guatapará, has 870 ha and is characterized by geological transition Basalt - Alluvial Deposit - Eluvial-Colluvial Deposit, concave and convex landforms and presence of Oxisols and Entisols. 371 samples were collected at a depth of 0-0.25 m for the evaluation of MS, clay content and BS. The incorporation of secondary information in geostatistical models was performed through the simple kriging with varying local means. For MS, information about geology and geomorphology were responsible for approximately 45% and 44% of its spatial continuity. For clay content, these results were higher, indicating 54% (geology) and 53% (geomorphology). For BS, there was no relation between secondary information and its spatial continuity. The incorporation of geological and geomorphology information to the MS data allowed a reduction of 44% and 37% in the number of samples required to represent the spatial pattern of the attribute. For clay content was verified the possibility of reducing by 35% the number of samples using both information. In the second stage of the study, average and standard deviation (uncertainty) maps of MS and clay content were calculated based on 200 realizations of the sequential gaussian ...